Unlocking the Potential of AI in Business: Challenges and Ethical Considerations - Giriraj Kiradoo (Recent Progress in Science and Technology Vol. 6, 2023)
Recent developments in AI technology have turned it into a tool that can completely revolutionise businesses. This research study aimed to investigate the application of AI in industry and the difficulties and ethical issues associated with its incorporation. After collecting data from a representative sample of business professionals, the research used qualitative and quantitative approaches to analyse the gathered information. According to the findings, artificial intelligence can assist businesses in automating repetitive tasks, increasing their efficiency, improving decision-making, and providing insights previously thought impossible. However, the research also uncovered many obstacles, such as a dearth of comprehension and specialised knowledge, high costs of implementation, and concerns regarding privacy and security. According to the study findings, businesses must consider ethical issues before implementing AI. These issues include accountability and transparency, the prevention of discrimination, and guaranteeing that AI aligns with human values. If businesses consider all of these factors, they will be competent to unlock the full potential of AI and use it to drive innovation, growth, and overall success.